Geohazard features of the Southern Sardinia - Paolo Emanuele Orrù; Valentino Demurtas; Antonietta Meleddu; Enrico Paliaga; Samuele Todde; Giacomo Deiana (Journal of Maps)
The Maps of Geohazard features of Southern Sardinia produced in the framework of the Magic project (MArine Geohazard along Italian Coasts) are here presented. The MaGIC project (Marine Geohazard along the Italian Coasts) had the aim of mapping the geohazard in the Italian seas. The features were derived from the digital elevation model interpretation of the seafloor morphology and shallow sub-surface. From the marine geo-hazards point of view, the main critical elements are represented by gravitational mass processes in the canyon heads, some of which, as in the Toro Canyon, are exposed to seismic triggering. In other cases, we observed that gravitational dynamics connected to fluid leakage processes (pockforms). Large landslides and debris avalanches have been detected in Cagliari Gulf, whereas in eastern upper slope, crescent bedforms, occurring in the eastern sector of the upper slope testify to the upward migration of hyperpycnal erosional structures linked to flows from nearby river inputs.